Monitoring of recent crustal movements around Cairo by repeated gravity and geodetic observations - ISSAWY, Elsayed A.; RADWAN, Anwar H.; DAHY, Sayed A.; RAYAN, Ali (Contributions to Geophysics and Geodesy, 2010)
The mass distribution and density inhomogeneities are one of the main factors affecting Earth’s dynamics. The temporal gravity variations were used to understand the surface tectonics and geodynamic modeling after the occurrence of an earthquake of 1992. The gravity field changes have been used for monitoring recent crustal movements in the area around Cairo and Southern part of Delta, Egypt. More than five successive gravity measurement campaigns were performed in parallel with the geodetic technique (GPS). The gravity changes were determined and correlated with seismic activity for all periods of observations. It was found that there is a certain relation shown by increasing of gravity values before the main seismic activity. As an example, a relatively considerable increase of gravity values was noticed for the network between the epochs of 2000 and 2004. Otherwise, the temporal gravity variations exhibited a considerable decrease in gravity values between the two campaigns of 2004 and 2007 for the same stations. This behavior could be explained by compressive deformation and strain buildup stage before the Southwestern Cairo earthquake (July 31, 2005 with magnitude of 4.3) and the stress release stage occurred after the main-shock. In addition, the results of geodetic measurements of the network around Cairo after five campaigns showed that the estimated horizontal velocities for almost of points are 5.5 mm/year in approximately NW direction.